Revitalisasi Pendidikan Pancasila untuk Generasi Z: Antara Literasi Digital dan Identitas Kebangsaan: Revitalizing Pancasila Education for Generation Z: Between Digital Literacy and National Identity - Sheylla Otta Lady Ramadhania; Dewi Sulistyawati; Miftakhul An-nisa Rohmawatun (Litera Academica Publishing, 2025)
Pancasila education as a means of internalizing national values faces new challenges in the digital era, marked by shifts in communication patterns, information consumption, and identity formation among youth. Generation Z, as “digital natives,” possesses high digital literacy but is susceptible to fragmented national identity due to exposure to global content. This study aims to explore how the revitalization of Pancasila education can balance digital literacy and the reinforcement of national identity for Generation Z. The research employs a qualitative multi-case study design in three urban secondary schools, involving in-depth interviews with students and teachers, observations of pedagogical practices, and analysis of curriculum documents. Findings reveal that successful Pancasila teaching strategies include (1) integration of digital-based project materials, (2) use of social media and interactive platforms as a medium for reflecting on national values, and (3) facilitation of critical dialogue between students’ digital experiences and Pancasila values. However, obstacles such as insufficient teacher competence in digital literacy, curricular resistance, and technological access disparity emerge. The study concludes that revitalizing Pancasila education for Generation Z requires adaptive curriculum design, digital literacy training for educators, and cross-stakeholder collaboration so that value education retains relevance in the digital context.